2022
DOI: 10.1530/eor-22-0042
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the clinical efficacy and safety of oblique lateral interbody fusion and transforaminal interbody fusion in the treatment of degenerative lumbar spondylolisthesis

Abstract: Objective The aim of this study was to comprehensively evaluate the efficacy of oblique lateral interbody fusion (OLIF) and transforaminal lumbar interbody fusion (TLIF) in the treatment of degenerative lumbar spondylolisthesis by meta-analysis. Methods A computer-based search of PubMed, Cochrane Library, Embase, Web of Science Core Collection databases, the China National Knowledge Infrastructure, China Biology Medicine, and Wanfang Digital Periodicals was conducted from the time of inception of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…NS options include oral and injectable pain medications and physical therapy. In contrast, surgical options include decompression only (DO), decompression plus fusion without internal fixation (DF), decompression plus fusion with internal fixation (DFI), endoscopic decompression plus fusion (EDF), endoscopic decompression (ED), and circumferential fusion (360F) 2 , 8 11 . However, the efficacy of different treatment strategies remains controversial 3 , 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…NS options include oral and injectable pain medications and physical therapy. In contrast, surgical options include decompression only (DO), decompression plus fusion without internal fixation (DF), decompression plus fusion with internal fixation (DFI), endoscopic decompression plus fusion (EDF), endoscopic decompression (ED), and circumferential fusion (360F) 2 , 8 11 . However, the efficacy of different treatment strategies remains controversial 3 , 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…33 Although it is an indirect decompression modality, OLIF has been shown to be clinically equivalent to Mis-TLIF for the treatment of DLS and DLSS. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] OLIF was performed through an oblique lateral approach. The intervertebral disk nucleus pulposus and cartilaginous endplate were thoroughly removed.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] To date, some studies have compared the clinical and radiologic outcomes of OLIF with Mis-TLIF or TLIF in patients with DLS or degenerative lumbar spinal stenosis (DLSS). [15][16][17][18][19][20][21][22][23][24][25][26][27][28] Although clinical efficacy comparable to Mis-TLIF or TLIF can be achieved, most studies have reported that posterior fixation is often required after OLIF to reduce the risk of cage displacement or subsidence. 29 However, compared with lateral fixation, posterior fixation can significantly increase OT and surgical trauma, thus making the surgery more cumbersome.…”
Section: Introductionmentioning
confidence: 99%
“…Transforaminal lumbar interbody fusion (TLIF) is a surgical method widely used to treat spinal diseases such as herniated discs, lumbar spondylolisthesis, and lumbar stenosis ( 1 , 2 , 3 ). With the rapid development of aging society and the influence of modern lifestyles, the incidence of these spinal diseases is gradually increasing.…”
Section: Introductionmentioning
confidence: 99%